Sprawa śmierci cesarza bizantyńskiego Romana III Argyrosa (1028-1034) - Kotala, Tomasz (Acta Universitatis Lodziensis. Folia Historica, 2005)
The objects of investigation of present article are the events from 1034 year, which brought to death of emperor Romanos III Argyros and change the appointment of the imperial throne in Byzantium. The essential reports in this matter are delivered by chronicles of Michael Psellos and John Skylitzes which indicate on poisoning, as main cause of emperor’s death. The other authors wrote directly about drowning the emperor in a palace pool, which had to bring to his decease at night from 11 to 12 April in 1034. Both remembered chronicles and the other mentioning about these events works pass the detailed symptoms of imperial disease peaceably. These symptoms were succesfully subordinated to the definite kinds of poisons, which confirmed the report about poisoning of Romanos III. The investigation does not confine on this, it also explains the contradictions in the source base relating to poisoning/ drowning. This turned out, that although we can to tell about the trial to murder the emperor during the time of bath only in the context of acceleration of his death, which and so would had happened inevitably as the result of the long-lasting passing the plant and metallic poisons. All these circumstances had their long-lasting cause in the conflict of Romanos 111 with his wife Zoe, who did not hesitate to bring to change on the imperial throne to bestow the imperial crown to young Michael the Paphlagonian, at whos side – as his wife - she wanted to stay on long as the empress of Byzantium.